Screening method and metabolic analysis of plant anti-aging microorganisms via ammonia-induced senescence in the duckweed Wolffia microscopica - Tan, Deguan; Fu, Lili; Yu, Ying; Sun, Xuepiao; Zhang, Jiaming (Frontiers in Plant Science, 2024)
Ammonium is the preferred N nutrition over nitrate for some plant species, but it is toxic to many other plant species and induce senescence at high concentrations. The duckweed Wolffia microscopica (Griff.) Kurz is the smallest and fast-growing angiosperm. It is highly sensitive to ammonium and has a short lifespan on media containing 0.5 mM or higher ammonia. This feature makes it a potential model plant to screen for anti-aging microorganisms. By co-culturing W. microscopica with endophytic microorgainisms isolated from rubber tree, we screened out an Aspergillus sclerotiorum strain ITBB2-31 that significantly increased the lifespan and the biomass of W. microscopica. Interestingly, both filter-sterilized and autoclaved exudates of ITBB2-31 increased the lifespan of W. microscopica cultures from 1 month to at least 7 months. Meanwhile, the exudates also showed strong anti-aging effects on cassava and the rubber tree leaves and increased chlorophyll contents by 50% -350%. However, high contents of filter-sterilized exudates inhibited the growth of W. microscopica while extending its lifespan, indicating that there were heat-sensitive growth-inhibiting agents in the exudates as well. Comparative metabolome analysis of the filter-sterilized and autoclaved exudates revealed multiple heat-stable antiaging and heat-sensitive growth-inhibiting compounds. Our results suggest that W. microscopica can be served as a rapid and efficient model plant to screen for plant anti-3 aging microorganisms.